A review of the influence of adding the word halal to popular food and drink which have non-halal connotations and excessive terms on muslim consumers - Putri, Tanti Amarta (Journal of Halal Product and Research (JHPR), 2024)
Nowadays, some people think that food is not merely a necessity but is a form of easy and cheap getaway amidst the hustle and bustle of a busy work schedule. The popularity of food is not only derived from the taste but also the name that attracts the attention of potential consumers. Naming foods without prohibited elements is starting to become a priority among food and beverage (F&B) businesses in Indonesia. One by one, well-known F&B businesses began to take steps to change the name of the menu which initially had unlawful elements into good ones. Lawful (halal) and good food, which can be seen from its ingredients, should not be given a bad name as a form of conduct that glorifies Allah, All-Provider. Even food/drinks inspired by foreign cultures that have names with non-halal connotations do not necessarily become halal by simply adding the term halal in front of it. This article aims to analyse people's behaviour in relations to how the naming of foods may be misleading yet attractive among Muslim consumers. This article uses secondary research methods as data collection to provide a comprehensive and credible understanding. Keywords: Naming Food, Food and Beverage, Halal